2005
DOI: 10.1111/j.0022-202x.2005.23788.x
|View full text |Cite
|
Sign up to set email alerts
|

BRAF and NRAS Mutations Are Frequent in Nodular Melanoma but Are not Associated with Tumor Cell Proliferation or Patient Survival

Abstract: Previous studies have shown frequent mutations in the BRAF (V-raf murine sarcoma viral oncogene homolog B1) or NRAS (neuroblastoma RAS viral [V-ras] oncogene homolog) genes in cutaneous melanoma, but the relationship between these alterations and tumor cell proliferation has not been examined in human melanoma. In our study of 51 primary nodular melanomas and 18 paired metastases, we found mutations in BRAF (codon 600, previously denoted 599) in 15 primary tumors (29%) and eight metastases (44%). The figures f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
92
3
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 18 publications
13
92
3
4
Order By: Relevance
“…However, GNAQ mutations have been shown to have similar frequencies at all clinical stages of uveal melanoma progression, and to be independent of chromosomal aberrations, hinting at GNAQ being an early or initiating oncogenic event (Onken et al, 2008). This is consistent with the assumption that frequent oncogenic mutations of BRAF and NRAS in cutaneous melanoma as well as in benign melanocytic nevi (Davies et al, 2002;Pollock et al, 2003), which also activate the MAP-kinase pathway, are early events and are not associated with clinical outcome (Shinozaki et al, 2004;Akslen et al, 2005;Edlundh-Rose et al, 2006).…”
Section: Discussionsupporting
confidence: 61%
“…However, GNAQ mutations have been shown to have similar frequencies at all clinical stages of uveal melanoma progression, and to be independent of chromosomal aberrations, hinting at GNAQ being an early or initiating oncogenic event (Onken et al, 2008). This is consistent with the assumption that frequent oncogenic mutations of BRAF and NRAS in cutaneous melanoma as well as in benign melanocytic nevi (Davies et al, 2002;Pollock et al, 2003), which also activate the MAP-kinase pathway, are early events and are not associated with clinical outcome (Shinozaki et al, 2004;Akslen et al, 2005;Edlundh-Rose et al, 2006).…”
Section: Discussionsupporting
confidence: 61%
“…Akslen et al evaluated 51 primary nodular melanomas. In this retrospective study NRAS mutation was found in 27% of patients [82]. RAS mutation was not associated with tumor cell proliferation by Ki-67 expression, tumor thickness, microvessel density, or vascular invasion, and there were no differences in patient survival [82].…”
Section: Is Nras a Prognostic Biomarker In Melanoma?mentioning
confidence: 56%
“…The effect of these mutations on clinical outcome remains uncertain [59,61,73,74]. Table 1 summarizes most important studies on the prognostic role of NRAS in melanoma [63,68,[74][75][76][77][78][79]61,[80][81][82][83]. The majority of these studies have been retrospective in nature, and most of them included patients with recurrent or metastatic disease.…”
Section: Is Nras a Prognostic Biomarker In Melanoma?mentioning
confidence: 99%
“…V600E mutations in our series comprised only 74% of total BRAF mutations compared with 85% to 100% in other series. 43,[57][58][59][60][61] This difference likely reflects the more narrowly focused assays used in other studies, although the greater sensitivity of the MassARRAY platform compared with conventional sequencing may also be a factor. Ongoing trials of BRAF inhibitors for the treatment of melanoma are enrolling only patients with BRAF V600E (PLX4032, Roche/Plexxikon), or V600E and V600K mutations (GSK2118436, GlaxoSmithKline).…”
Section: Discussionmentioning
confidence: 99%